Effects of a Multimodal Exercise Program Plus Neural Gliding on Postural Control, Pain, and Flexibility of Institutionalized Older Adults: A Randomized, Parallel, and Double-Blind Study. Issue 1 (January 2020) - Mateus, Ana; Rebelo, Jessica; Silva, Anabela G.
Abstract : Background and Purpose: The effect of adding neural mobilization to a multimodal program of exercises has not been investigated, despite its potential positive effects. The aim of this study was to compare the acute effects of a multimodal exercise program and neural gliding against a multimodal exercise program only, on pain intensity, gait speed, Timed Up and Go (TUG) test, lower limb flexibility, and static balance of institutionalized older adults. Methods: Older adults who were institutionalized (n = 26) were randomized to receive a multimodal exercise program plus neural gliding or a multimodal exercise program only. Both interventions were delivered twice a week for 8 weeks. Participants were assessed for pain, gait velocity, balance, flexibility, and TUG at baseline and postintervention. Results: A significant main effect of time for pain intensity ( F 1, 24 = 8.95, P = .006), balance ( F 1, 24 = 10.29, P = .004), and gait velocity ( F 1, 24 = 5.51, P = .028) was observed, indicating a positive impact of both interventions. No other significant effects were found (TUG and flexibility; P > .05). Discussion: A 45-minute multimodal exercise program, twice a week for 8 weeks, has a positive impact on pain intensity, balance, and gait velocity, but neural gliding has no additional benefit. It is unclear whether dose and type of neural mobilization may have had an impact on results. Considering the structural and physiological changes that tend to occur with age, future studies could explore the effects of neural tensioning or of higher doses of neural mobilization. Conclusions: This study suggests that adding neural gliding to a multimodal exercise program has no additional benefit.